Evaluation of the practice of applying state price regulation methods: Indian experience - E. A. Santovich (Управление)
In order to generalize foreign experience in the field of state price policy, the practical experience of the Republic of India on the use of state price regulation tools has been considered. A review of the legislation has been conducted, the mechanism has been revealed, and the pros and cons of certain state price control measures have been highlighted, in particular the use of a list of vital goods, the establishment of a mandatory maximum market price for all packaged goods, and the protection of the competitive environment of the national market. The results of the state policy of price regulation, as well as the dynamics of key indicators of the Indian economy over the past five years have been analysed. Further prospects and directions of development of the economy of the Republic of India have been outlined.The scientific research methodology has been based on a systems approach. Depending on the nature of the problems being developed, the methods of causal analysis, economic-statistical, monographic, abstract-logical and comparative have been applied. The regulatory legal acts of the Republic of India, statistics, electronic resources, as well as operational primary information of the ministries and departments of the Central Government of India make up the information base of the study.It has been concluded, that the state-built model of price regulation provides protection not only to consumers, ensuring the availability of necessary goods, but also to producers, ensuring redistribution of profit in their favor. The problems of the functioning of individual instruments of the state pricing policy have been indicated, however, based on statistical data, a generalized conclusion has been made, that they are not critical and do not undermine the country’s economy or the free functioning of the market. The prospects for the use of certain elements of the state price policy of India in the Russian economy have been evaluated.